TTHE EFFECT OF LEVERAGE, FIRM SIZE, PROFITABILITY, AND OPERATING ACTIVITIES ON EARNINGS QUALITY OF CONSUMER NON-CYCLICALS LISTED ON IDX - Heskya Lintang Surya Andhini; Beby Hilda Agustin; Imarotus Suaidah (SOSIOEDUKASI, 2026)
This study examines the effects of leverage, firm size, profitability, and operating activities on the earnings quality of Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange (IDX) during 2021–2025. This sector was chosen because its relatively stable demand provides a suitable context for assessing earnings quality. Secondary data from annual financial statements were analyzed using multiple linear regression on 205 firm-year observations obtained through purposive sampling. The findings indicate that leverage has no significant effect on earnings quality. In contrast, firm size has a significant positive effect, whereas profitability and operating activities have significant negative effects. Collectively, the independent variables significantly explain earnings quality, with an adjusted coefficient of determination of 20.7%. These results broaden empirical evidence on earnings quality within the Consumer Non-Cyclicals sector and provide useful considerations for investors, corporate managers, and other stakeholders when evaluating the credibility of reported earnings.